ANALISIS PENERAPAN METODE ACTIVITY BASED COSTING TERHADAP TARIF RAWAT INAP PADA RUMAH SAKIT UMUM KASIH BUNDA - Mulyanti, Dwinta; Bagianto, Agus (LPPM Universitas BSI, 2013)
ABSTRACT - Use of the estimated cost of hospitalization rates were based on General Hospital competitor rates imposed by Mother Love General Hospital, causing the gap between the cost of the facilities provided, and therefore to reduce this gap required a method to calculate the rates can provide cost information accurately. Overcome this method of activity-based costing can be used because the charge in accordance with the selection of activities undertaken appropriate cost driver. The method used is descriptive quantitative method, with the presentation of the data in the form of the costs in the form of numbers processing using mathematical formulas. The results showed that rates calculated using activity based costing method is greater than the rate that had been used by Mother Love General Hospital of Rp 454,226, while the rates in effect at the General Hospital Mother Love Rp 125,000. This is because rates Kasih Bunda Hospital is not a standard cost estimate for the result obtained from another hospital rates, while the rates based on activity based costing methods derived from calculations based on the activities performed in the inpatient activities. Keywords: activity based costing method, hospitalization rates